Front End Design Of Design Asset Sales Information System With Human Centered Design (HCD) Approach - Pratiwi, Putu Yudia; Kertiyasa, Made Medhi Premana; Indradewi, I Gusti Ayu Agung Diatri (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
As digital technology advances, online competition intensifies, yet many SMEs lack reliable, user-friendly systems. SME development often skews toward back-end optimization, while user-centered front ends remain underexplored. This study addresses that gap by designing and evaluating the front end of CV Bello Design’s digital design-asset sales platform and distilling UI/UX decisions transferable to similar SMEs. Using a Human-Centered Design (HCD), we mapped problems with the owner, staff, and past buyers, translated insights into personas and user flows, and iterated prototypes for customer and admin roles. Usability was assessed through user testing measuring effectiveness and satisfaction. In addition, a Heuristic Evaluation was conducted by experts to identify usability issues and opportunities for improvement. Test results show customer effectiveness of 93.75% and admin effectiveness of 95%. Relative efficiency reached 0,02948 goals/second for customers and 0,00939 goals/second for admins. Overall, users reported positive satisfaction. Heuristic findings highlighted needs for a login form, clearer transaction details and history, consistent currency symbols, richer product detail views, clear required-field cues, and an FAQ. Implemented fixes clarified transaction pages, standardized currency symbols, added required-field indicators, and provided an FAQ. Overall, the HCD-based interface measurably improves task completion and offers reusable design patterns for SME, web-based asset-sales platforms.